HAM dan Sistem Peradilan Pidana di Indonesia: Hak-Hak Narapidana dan Pemenuhannya Berdasarkan Peraturan Perundang-Undangan - Alya Deswitha Martha; M Fariz Raya Reswara; Muhammad Rais Aji Aras Kurniawan; Shophie Aulia Mumtazah; Tifany Putri Shaori; Prima Jaya Perdana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Correctional institutions are very important in the Indonesian criminal justice system. Here, prisoners receive education and training to reintegrate into society. They still have the same basic rights. This concept evolved from the changing values and goals of the criminal justice system. Indonesia is transitioning to restorative justice to transform prisoners into mentally and physically healthy individuals, who can contribute to society. The protection of the basic rights of prisoners is an obligation in every correctional institution. This is not only because it is a human right of prisoners, but it is also regulated in the Corrections Act. Furthermore, the realization of these basic rights can help the education and development process of prisoners in correctional institutions.